ANALISIS FAKTOR-FAKTOR PADA PERATAAN LABA - minadi wijaya; Krisnhoe Sukma Danuta Krishnoe (FEB UNWIKU PURWOKERTO, 2021)
The practice of income smoothing is a form of dysfunctional behavior in earnings management that is rife in this era of rapid business development, where managers intentionally change the company's financial statements with the aim of flattening the value of the company's earnings over several periods to make it look stable. The practice of perataan laba is considered as a solution to the very unstable profit conditions. This study aims to examine the effect of cashholding, net profit margin, and financial leverage on income smoothing. The population in this study were 44 banking subsector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The sampling method uses a purposive sampling technique and produces a sample of 37 companies. The results of this study indicate that net profit margin has a significant negatif effect on perataan laba, while cashholding and financial leverage have no significant effect on income smoothing